The effects of dietary intervention on HIV dyslipidaemia: a systematic review and meta-analysis. - Clare Stradling; Yen-Fu Chen; Tracy Russell; Martin Connock; G Neil Thomas; Shahrad Taheri (PLoS ONE)
Background Efficacy of dietary intervention for treatment and prevention of HIV-related lipid disturbances has not been well established. Methods We conducted a systematic search of electronic databases supplemented with manual searches and conference abstracts, without language restriction. All randomised controlled trials (RCTs) with blood lipid outcomes, involving dietary intervention or supplementation for the treatment or prevention of adult HIV dyslipidaemia, versus no or other intervention were included. Two authors using predefined data fields, including study quality indicators, extracted data independently. Results Eighteen studies (n = 873) met our inclusion criteria. Seven RCTs for omega-3 supplementation (n = 372), and four RCTs for dietary intervention (n = 201) were meta-analysed using random-effects models. Mild statistical heterogeneity was observed. Dietary intervention reduced triglyceride levels by -0·46 mmol/l (95%CI: -0·85 to -0·07 mmol/l) compared to control. Omega-3 supplementation reduced triglyceride levels by -1.12 mmol/l, (95%CI: -1·57 to -0·67 mmol/l) and total cholesterol, -0·36 mmol/l (95%CI: -0·67 to -0·05 mmol/l) compared to placebo/control. Conclusions Both omega-3 supplementation and dietary intervention reduced triglyceride level, with the latter possibly to a smaller extent. While dietary interventions are beneficial, more stringent dietary approaches may be necessary to fully address lipid disturbances in HIV patients. Trial registration PROSPERO 2011:CRD42011001329.